2022
DOI: 10.3389/fpls.2022.1003471
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and validation of blade parameters for inter-row weeding wheel in paddy fields

Abstract: The performance of existing rice-paddy weeding machines is not optimal. In this study, the influence of the installation angle of the weeding-wheel blade on cutting resistance and soil-slippage ability was analyzed. The optimal blade angle of the weeding wheel (i.e., the angle at which the resistance to the weeding wheel is minimal and the disturbance speed of the soil maximal) was shown to be< 20°; numerical simulation showed the actual optimal value to be 0°. Different weeding depths (30, 40, and 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…As the dynamic blade install angle increases beyond 0 • , the dynamic blade shifts from its penetration into the soil to pressing into the soil, leading to an increase in the coupling stress. This observation aligns with the findings of Zhang et al [22].…”
Section: Results Of Simulation Testssupporting
confidence: 94%
See 1 more Smart Citation
“…As the dynamic blade install angle increases beyond 0 • , the dynamic blade shifts from its penetration into the soil to pressing into the soil, leading to an increase in the coupling stress. This observation aligns with the findings of Zhang et al [22].…”
Section: Results Of Simulation Testssupporting
confidence: 94%
“…Wang et al [21] designed a remotely controlled inter-row weeding machine capable of removing two rows of weeds in one pass, achieving a weeding rate of no less than 77.9%. Zhang et al [22], through simulation software, optimized the angle of the rake teeth based on the resistance it encountered and the velocity of the soil particles, resulting in a weeding rate of 88.2%. However, the inter-row weeding wheels used in these machines are passively rotating or electrically driven and rely on the weeding wheel tines to bury or pull out weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the tea particles fall onto the pot groove' surface which entails collision movement. Ignoring the collision effect generated between tea particle and other particle, tea particle were treated as a single mass point, and a mathematical model of the motion characteristics of tea particle in air then established by following the principle of fluid dynamics; it was used to carry out a kinetic analysis of the motion process of tea particles (Zhang et al, 2022).…”
Section: Analysis Of the Movement Process Of Tea Particlesmentioning
confidence: 99%
“…Consequently, a series of studies on technical aspects and methods for utilizing paddy field machinery have been conducted by researchers [28][29][30][31][32][33][34][35][36][37]. Zhang, Y. et al [38] optimized the operational parameters of a weeder blade used in rice fields, and their results demonstrated that the optimized blade achieved satisfactory performance according to agronomic requirements. Zhu, D. et al [39] employed finite element and discrete element methods to develop a dynamic model for the coupled system of blade-straw-rice soil, with a focus on analyzing the operational processes of blades in paddy fields.…”
Section: Introductionmentioning
confidence: 99%